Construction method of double unicast network coding - Baoxing PU; Zhiyi MO (Tongxin xuebao)
In order to use network coding technology for data transmission in double unicast network,a construction method of double unicast network coding was proposed.The pre-coding strategy was implemented at each source node,the random linear network coding combined to the multi-objective optimization evolutionary algorithm was adopted to design the local coding vector of each channel.At the each sink node,the base vector of zero space of matrix was used to eliminate some information interference,and then the two-level pre-coding strategy was used to control the transmission rate at source.Thus,each sink node could be decoded successfully.With the proposed method,the approximate reachable information rate region of double unicast network coding could be determined and the transmission scheme for each vector in the reachable information rate region could be designed.Theoretical derivation and simulation calculation show the effectiveness of the proposed method.